PENINGKATAN KESADARAN KARAKTER KEWARGANEGARAAN MAHASISWA MELALUI PEMANFAATAN E-MODUL DAN PEMBELAJARAN BERBASIS CIVIC ENGAGEMENT DI INSTITUT SENI INDONESIA PADANGPANJANG - Thania, Tira; Fadli Ilham, Windi Eka Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to enhance students’ citizenship character awareness through the utilization of an e-module and civic engagement-based learning at Institut Seni Indonesia Padangpanjang. The research was motivated by pre-study findings indicating low student ability to integrate citizenship values into artistic works, with 41.4% of students experiencing difficulty and 51.7% lacking understanding of these values. The study employed a Research and Development (R&D) approach using the ADDIE model, including analysis, design, development, implementation, and evaluation stages. Data were collected through expert validation, student questionnaires, interviews, and analysis of student works and reflections. The e-module validation results indicated a very high level of validity in terms of content, media, and language, making it suitable for learning implementation. Implementation through digital social campaign projects demonstrated increased participation, creativity, collaboration, and students’ ability to connect national issues with the arts and cultural contexts. These findings reveal that the combination of the e-module as a theoretical framework and civic engagement as practical application is effective in strengthening students’ citizenship character awareness. This study contributes to the development of innovative learning models in arts higher education that contextualize national values through creative practice. Keywords: Civic Education, Student Character, Civic Engagement, E-Module, Arts Education